Flyte - Sage, Angie (Sage, Angie. Septimus Heap, 2007)
When Princess Jenna is pursued by a dark wizard, it is the apprentice, Septimus Heap, who must save her while enduring such terrors as a night in the Forest with hungry wolverines and carnivorous trees.